New experimental bremsstrahlung cross-section for light ion beams up to 60 MeV and comparison to theoretical models. (February 2023) - Ralite, Flavien; Koumeir, Charbel; Guertin, Arnaud; Haddad, Ferid; Mouchard, Quentin; Servagent, Noel; Metivier, Vincent
Abstract: Recent works focused on bremsstrahlung radiation as a non-invasive tool for monitoring proton beams used in radiobiology (>20 MeV). In order to study the validity of theoretical models of bremsstrahlung cross sections, bremsstrahlung X-rays between 4 keV and 15 keV coming from a carbon target irradiated by proton beams in the energy range from 15 MeV to 50 MeV were measured by a silicon drift detector. The obtained data vary from 10 mb keV −1 to 1000 mb keV −1 and fit well the literature and with theoretical model calculation. These results strongly support that bremsstrahlung X-rays models can be used to develop promising online tools for proton beam monitoring. Highlights: Bremsstrahlung cross sections for light ion beams are significant. Cross section measurements fit the theoretical models for beam energy up to 50 MeV. The Bremsstrahlung X-rays can be a tool to monitor light ion beams.